The Role of Social Infrastructure in Rural Areas’ Sustainable Development Processes - Leszek SZCZUPAK (Communications of International Proceedings, 2021)
The aim of this paper was to point out at social infrastructure as at one of the most significant, and, at the same time, indispensable and most effective factors of sustainable development of rural areas. Social infrastructure is made up of a network of closely connected utilities and institutions (education, culture, healthcare system, tourism, physical education) realizing defined social needs, which, in general, fluctuate and grow in terms of quality and quantity, along with economic development of a state and its particular regions. Functioning of elements creating social infrastructure also enables realization of social policy in the area of shaping (improving) living conditions of a population and forming social order. In the following publication, the role of infrastructure, especially social infrastructure, was shown as one of fundamental factors determining the pace of ongoing developmental processes of rural areas, and guaranteeing their convergence process. Research results concerning the assessment of rural areas residents’ satisfaction with services provided by basic components of social infrastructure have also been presented in the article. The method of no probability (non-random) sampling based on the knowledge of a structure of a researched population has been used.
Keywords: Rural Areas; Social Infrastructure; Sustainable Development